High levels of burnout and depression in a population of senior dental students in a school of dentistry in Korea - Eun-Jung Kwak; Young-A Ji; Seung-Ho Baek; Yoo Sang Baek (Elsevier, 2021)
Background/purpose: Dental students are exposed to highly stressful environments, making them high-risk for burnout and depression. This study intended to investigate the burnout and depression level in senior dental students in Korea. Materials and methods: We conducted a cross-sectional questionnaire study among third- and fourth-year dental students enrolled at Seoul National University. Demographic data, Maslach Burnout Inventory (MBI), Patient Health Questionnaire (PHQ-9), dental education satisfaction, and counseling needs were measured. Statistical analyses included intergroup comparison of MBI subscales (emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA)) to identify the risk factors for burnout. Correlation analyses between MBI subscales and PHQ-9 were also conducted. Results: Among 112 students included in the study, 44.6% had high EE, 36.6% showed high DP, and 51.8% had low PA. There were 20 (17.9%) students who satisfied burnout criteria on all three subscales. There were 19 (17.0%) students with PHQ-9 scores of 10 or greater. There were no significant differences in MBI subscales or PHQ-9 scores according to sex, study year, marital status, funding for studies, or academic grade, but there was a difference according to academic workload. All MBI subscales had significant correlation with PHQ-9 score. Burnout students reported significantly lower satisfaction scores and greater need for counseling compared to non-burnout students. Conclusion: Burnout and depression levels among dental students in Korea were relatively high and intercorrelated. Burnout level was significantly associated with high academic workload. Students experiencing burnout were likely to be dissatisfied with their education programs and likely to need counseling.